NMR Binding and Functional Assays for Detecting Inhibitors of S. aureus MnaA. (July 2016) - Hou, Yan; Mayhood, Todd; Sheth, Payal; Tan, Christopher M.; Labroli, Marc; Su, Jing; Wyss, Daniel F.; Roemer, Terry; McCoy, Mark A.
Nonessential enzymes in the staphylococcal wall teichoic acid (WTA) pathway serve as highly validated β-lactam potentiation targets. MnaA (UDP-GlcNAc 2-epimerase) plays an important role in an early step of WTA biosynthesis by providing an activated form of ManNAc. Identification of a selective MnaA inhibitor would provide a tool to interrogate the contribution of the MnaA enzyme in the WTA pathway as well as serve as an adjuvant to restore β-lactam activity against methicillin-resistant Staphylococcus aureus (MRSA). However, development of an epimerase functional assay can be challenging since both MnaA substrate and product (UDP-GlcNAc/UDP-ManNAc) share an identical molecular weight. Herein, we developed a nuclear magnetic resonance (NMR) functional assay that can be combined with other NMR approaches to triage putative MnaA inhibitors from phenotypic cell-based screening campaigns. In addition, we determined that tunicamycin, a potent WTA pathway inhibitor, inhibits both S. aureus MnaA and a functionally redundant epimerase, Cap5P.